2008
DOI: 10.1007/s12010-008-8256-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of Response Surface Method for Studying the Role of Dissolved Oxygen and Agitation Speed on Gamma-Linolenic Acid Production

Abstract: To study the effect of agitation speed (rpm) and dissolved oxygen concentration (DO) on the production of gamma linolenic acid by Mucor sp. RRL001, a central composite design experiment was performed in a 5-L stirred tank bioreactor. The design consisted of a total of 10 runs consisting of runs at five levels for each factor and was divided in two blocks. The ANOVA analysis and Pareto chart of effects suggested agitation speed (p = 0.0142) linear effect and DO concentration (p = 0.0342) quadratic effects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In this study, the GLA content of TFAs was significantly increased with certain amino acids, particularly with proline for AUMC 11616.A and tryptophan for AUMC 6696.A. In other studies, GLA has been shown to play an important role in humans, improving the health of patients suffering from diabetes, aging, cancer, and immune diseases ( 26 , 41 ). The highest yield of GLA in this study was significantly more than that obtained from other species of Mucorales and some other Zygomycotina, which are considered potential candidates for the application in the industrial production of PUFAs and other valuable compounds ( 34 ).…”
Section: Discussionsupporting
confidence: 54%
“…In this study, the GLA content of TFAs was significantly increased with certain amino acids, particularly with proline for AUMC 11616.A and tryptophan for AUMC 6696.A. In other studies, GLA has been shown to play an important role in humans, improving the health of patients suffering from diabetes, aging, cancer, and immune diseases ( 26 , 41 ). The highest yield of GLA in this study was significantly more than that obtained from other species of Mucorales and some other Zygomycotina, which are considered potential candidates for the application in the industrial production of PUFAs and other valuable compounds ( 34 ).…”
Section: Discussionsupporting
confidence: 54%
“…Because all of the experiments were conducted under the same operating conditions excluding the aeration rate, increase in growth and GLA content with changes in the aeration rate are attributed to improved mixing and better oxygen availability. It is well documented that dissolved oxygen is essential for the desaturation of linoleic acid (C18:2) by Δ-6-desaturase in the production of GLA (1, 23). It is significant to attribute this cause to increase in oxygen availability, promoting both growth and the production of GLA by the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…NADPH-cytochrome b 5 reductase, cytochrome b 5 , and a terminal desaturase, are involved in the synthesis of unsaturated fatty acids (6). In addition, oxygen is also required for unsaturated fatty acid synthesis (1). In algae, the desaturation of linoleic acid (C18:2 ω6) is facilitated by either Δ-6 desaturase or Δ-15-desaturase, resulting in the production of 18:3ω6 or 18:3ω3, respectively; these fatty acids ultimately form higher PUFAs, viz.…”
Section: Introductionmentioning
confidence: 99%
“…Higher aeration rates are usually bene cial for cell growth by improving mass transfer of substrate, product and oxygen and enhancing the oxygen availability since oxygen is an electron acceptor [20]. Agitation can also facilitate the transfer of mass and heat in the reactor, but high agitation rate will inevitably cause stronger shear forces, leading to morphological changes and might even damage the cell structure [21,22]. In this study, the effect of different DO concentrations expressed as partial pressure of oxygen (pO 2 ) regulated by agitation and aeration on cell growth, lipid production, POA accumulation and ethanol generation were comprehensively investigated.…”
Section: Introductionmentioning
confidence: 99%